Repairing and Enhancing Trust:Approaches to Reducing Organizational Trust Deficits - Kramer, Roderick M.; Lewicki, Roy J. (Academy of Management Annals, 2010)
Organizational scholars have long touted the myriad benefits of trust for organizational functioning and performance. Recent surveys, however, document pervasive deficits in such trust. This article addresses the important topic of reducing these deficits. Our attack on this problem is two pronged. First, we examine approaches to repairing damaged trust within organizational settings. Specifically, we assess the state of organizational theory and knowledge regarding effective approaches to trust repair after internal or external events have weakened or damaged trust in an organization. We define what is meant by trust repair, review the most common ways that trust is broken, and then explore the three major approaches that have received the most attention in trust‐repair research. We then address the question of how trust, once repaired, can be enhanced and made more durable and stable. Specifically, we examine theory and evidence regarding the antecedent conditions that support the development and maintenance of what we term presumptive trust among organizational members. We conclude the article with some recommendations of fruitful directions for future research.